4.B. Skills building seminar: Participatory action research: sharing power to improve public health research outcomes. (30th September 2020) - ,; ,
Abstract: This skills building seminar addresses the use of Participatory Action Research (PAR) as strategy to involve professionals and practitioners from (non-academic) health organizations in public health research. These so-called stakeholders possess external -experiential practice-based- knowledge important for a successful realization of a public health research project. After a short introduction on the why and when of PAR as a suitable strategy in public health research, and the why and when in a project's life cycle stakeholders can or must join, levels of participatory practices will be discussed, as well as consequences of transfer of power from academic researchers to professionals and practitioners in the field. The first part of the seminar will be followed by two real life examples from two projects in Germany: 1) a psycho-oncological care project -hospital-based-, where alarm bells went off during the external prospective evaluation of the new care programme. In the development phase of this new programme, key stakeholders had not been involved yet; and 2) the optimization, by inserting PAR cycles, of a stroke family caregiver support programme before implementation in a public health care system. The audience is invited to discuss research dilemmas, as well as pros and cons of the PAR strategy Key messages: Participatory action research is about active collaboration between academics and health professionals to bring transformative change through the process of taking action and doing research. Sharing power between academics and health professionals is vital to improve public health research.